Development of a patient-centered video series to improve education before kidney transplantation. Issue 9 (September 2018) - Rosaasen, Nicola; Mainra, Rahul; Kukha-Bryson, Azaad; Nhin, Victoria; Trivedi, Paraag; Shoker, Ahmed; Wilson, Jay; Padmanabh, Raj; Mansell, Holly
Highlights: Poor patient knowledge is a problem after transplant. The development of an educational intervention is described. Patient-oriented research led to unexpected changes in the project. Patient involvement is necessary for high quality, relevant educational interventions. Abstract: Background: Inadequate patient knowledge about transplantation can result in low patient satisfaction and contribute to poor clinical outcomes. The purpose of this patient-oriented research project was to develop an educational intervention for patients awaiting kidney transplantation. Methods: An educational intervention was developed by patients and health care providers, experts in medication adherence, video education, motivational psychology, and cultural education. Project objectives were defined and content was guided by a series of studies conducted with stakeholders. A review process was undertaken with additional patients, external health care providers and ninth grade high school students and edits were applied accordingly. Results: A set of six educational videos, ranging in length from 3 to 24 min, was created to describe the transplant process. The videos are patient friendly in design, and incorporate animations to explain complex information to accommodate low health literacy, and patient testimonials align the content with principles of adult learning theory. Feedback from external patient reviews [n = 8], external care providers [n = 13] and students [n = 26], indicate that the mini-series is informative and useful. Conclusion: Patient involvement significantly influenced the development of a video series about kidney transplantation. Practice Implications: Patient engagement is integral for developing high quality and relevant educational interventions.